Maternal Mortality : Report June, 1932 (London : The Maternal Mortality Committee)
1932-06 1932 1930s 20 pages COUNTY BOROUGHS There are eighty-four County Boroughs. Reports from all these have been analysed. (1) The appointment of Health Visitors, whose duties include attendance at an Ante-natal and Post-natal Centre, and the visiting of expectant mothers. All have Health Visitors. (2) The establishment of Ante-natal Clinics for expectant mothers, and of Post-natal Clinics which mothers can attend immediately after confinement. Eighty County Boroughs have established ante-natal clinics. (3) Assistance to Midwives. (a) Provision of sterilised maternity outfits free or at cost price. Only twelve Borough Councils provide these. This figure does not include "bags" lent. (b) A subsidy to enable a midwife to practise in a district which would otherwise not support her. Twelve County Boroughs operate this. (c) The appointment, where necessary, of municipal midwives. This power is used by eleven only. We have only included midwives employed by municipal hospitals or nursing homes where these are specifically stated to be working on a district. (d) The payment of part fees to a midwife when the patient cannot afford the full fee. Thirty-one Boroughs appear to use this power. Several Authorities have an insurance scheme for mothers who may need the services of a doctor. (e) "Refresher" courses for practising midwives. Definite courses of lectures are provided by seven Borough Councils. We have not included odd groups of lectures to Health Visitors, &c., but only cases in which a definite postgraduate course is mentioned. (4) Maternity Homes or beds in a Maternity Hospital for :— (a) Complicated cases. (b) Patients whose home circumstances are unsuitable for a confinement at home. (c) Ante-natal observation. (d) The treatment of puerperal sepsis. (a) Sixty-seven Boroughs state they have beds. (b) Fifty-nine Boroughs have beds. It is particularly difficult to get an accurate idea of this number as only a certain (8) 292/824/1/58